Seroprevalence and risk factors of bluetongue virus infection in sheep and goats in West Gondar zone, Northwest Ethiopia - Beyan, Adem; Molla, Wassie; Molla, Adugna Berju; Birhan, Mastewal; Ibrahim, Saddam Mohammed; Dessalegn, Bereket; Kenubih, Ambaye; Gessese, Abebe Tesfaye; Kinde, Mebrie Zemene; Dagnaw, Gashaw Getaneh; Fenta, Melkie Dagnaw; Tesfaye, Hana; et al. (Frontiers in Veterinary Science, 2025)
IntroductionBluetongue is a non-contagious arthropod-borne viral disease that affects ruminants. No investigations have yet been conducted to ascertain the seroprevalence and associated risk factors of bluetongue in Northwest Ethiopia. It is essential to determine the seroprevalence and correlated risk elements to formulate an effective strategy for preventing and surveillance of the disease.MethodsA cross-sectional study was carried out between February 2023 and May 2023 to determine the seroprevalence and risk factors associated with Bluetongue virus (BTV) in sheep and goats in the selected districts of West Gondar zone. A multistage cluster sampling technique was employed, with zones and districts purposively selected, and kebeles within these districts chosen through simple random sampling. Villages were treated as clusters. A total of 444 blood specimens were collected from the sheep and goats and subsequently tested for BTV antibodies using a commercially available competitive enzyme-linked immunosorbent assay kit. A mixed-effects logistic regression was employed to evaluate the relationship between Bluetongue virus seropositivity and potential risk factors.ResultsThe overall seroprevalence rate at the individual animal level was 84.5% (95% CI: 81.09–87.82). The seroprevalence in sheep and goats was 83.8% (257/308) and 86.8% (118/136), respectively. Species and age were significant risk factors for BTV seropositivity in the study area (p < 0.05). Adult and older sheep and goats exhibited 3.49 (95% CI: 1.90–6.41) and 25.95 (95% CI: 9.45–71.28) times higher seroprevalence with the bluetongue virus in comparison to their younger counterparts, respectively.DiscussionIn conclusion, the current findings showed that BTV is highly prevalent. The specific circulating BTV serotypes and the temporal pattern of Bluetongue in the study area remain unknown, necessitating further investigation.